Increased Levetiracetam Clearance and Breakthrough Seizure in a Pregnant Patient Successfully Handled by Intensive Therapeutic Drug Monitoring. Issue 3 (June 2015) - Cappellari, Alberto M.; Cattaneo, Dario; Clementi, Emilio; Kustermann, Alessandra
Abstract : Abstract: We report a 36-year-old pregnant patient with subtherapeutic trough plasma levels of levetiracetam (LVT) and a breakthrough nocturnal seizure while assuming 3 times a day dosing of the drug. An intensive pharmacokinetic study was performed from immediately before to 11 hours after the morning LVT dose administration and suggested that the patient was not adequately exposed to the drug during the night. After changing the dosing of LVT to 4 times a day, the patient experienced no seizures and delivered a healthy newborn without complications. Afterward, trough plasma levels of LVT remained always within the therapeutic range until delivery, and no major increase of the drug daily dose was required.